(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2009)
On the basis of conducted field geological, petrographic investigations the magmatic origin of carbonatites of the Sevan ridge is proved, which previously were considered as contact-metasomatic formations – listvenites. These are a new type of carbonatites, which are spatially and in all probability genetically related to ultramaphic complex of Amasia-Sevan-Akera ophiolit zone, without any attributes of connectivity with alkaline rocks formation. It is significant that these carbonatites appear with the presence of accessory minerals of spinell group.